2016
DOI: 10.1016/j.diagmicrobio.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Screening for abnormal vaginal microflora by self-assessed vaginal pH does not enable detection of sexually transmitted infections in Ugandan women

Abstract: Self-measured vaginal pH correlated well with markers of high-risk microflora types such as BV or aerobic vaginitis, but not with STIs. Hence, in a screening program addressing AVF in low-resource countries, extra specific tests are required to exclude STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…Apart from BV, which is found to be highly prevalent in most sub-Saharan African countries [ 24 ], the prevalence of AVF and AV has not been intensively studied in Africa yet. In South Africa and Uganda, however, it was clearly shown that AVF and AV are more frequent than in other parts of the world [ 25 , 26 ] and presumably account for many of the potential side effects and STI transmission risk factors allegedly accounted to BV in several former studies [ 24 , 27 ]. We currently did not find a clear association between cytology/positive HR-HPV and disrupted flora types such as AV or BV as Jahic, Vieira-Baptista, and Donders found [ 28 , 29 ], but this can most likely be accounted to small numbers and pleas for more extensive research.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from BV, which is found to be highly prevalent in most sub-Saharan African countries [ 24 ], the prevalence of AVF and AV has not been intensively studied in Africa yet. In South Africa and Uganda, however, it was clearly shown that AVF and AV are more frequent than in other parts of the world [ 25 , 26 ] and presumably account for many of the potential side effects and STI transmission risk factors allegedly accounted to BV in several former studies [ 24 , 27 ]. We currently did not find a clear association between cytology/positive HR-HPV and disrupted flora types such as AV or BV as Jahic, Vieira-Baptista, and Donders found [ 28 , 29 ], but this can most likely be accounted to small numbers and pleas for more extensive research.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from vaginal lavage was extracted, and PCR amplification and sequencing targeting the V4 regions of the 16S rRNA gene were performed on a HiSeq2500 (Illumina, San Diego, CA, USA). Bioinformatics analysis and results were already reported in a previous study [ 15 ].…”
Section: Methodsmentioning
confidence: 77%
“…However, several factors limit the broad application of wet-mount microscopy score. First, cells and bacteria can move on saline smears, the long-term preservation of wet-mount smears because repeated review by rehydration is less commonly practiced [ 15 , 16 ]. Second, the identification of aerobes requires a keen microscopist and a phase-contrast microscope, which may be obstacles to wide application in clinical practice in underdeveloped regions and the development of artificial intelligence (AI) interpretation systems.…”
Section: Introductionmentioning
confidence: 99%
“…oder Mycoplasma hominis, die weder durch eine mikroskopische Diagnostik noch durch eine pH-Wert-Bestimmung erfasst werden und einer gezielten Diagnostik bedürfen [43]. Ureaplasma urealyticum war in einer Kohorte von 126 Frauen mit vorzeitigen Wehen in über 60 % nachweisbar, wobei sich keine Unterschiede in der Häufigkeit zwischen Frauen mit und ohne nachfolgender Frühgeburt fanden [44].…”
Section: Diskussionunclassified
“…Trotzdem fehlt für die Durchführung von Abstrichkontrollen im vorliegendem Kontext jegliche Evidenz. Uneinheitlich waren die Meinungen zur Therapieindikation bei Nachweis intrazellulärer Erreger wie Ureaplasma urealyticum oder Mycoplasma hominis, die weder durch eine mikroskopische Diagnostik noch durch eine pH-Wert-Bestimmung erfasst werden und einer gezielten Diagnostik bedürfen [43]. Ureaplasma urealyticum war in einer Kohorte von 126 Frauen mit vorzeitigen Wehen in über 60 % nachweisbar, wobei sich keine Unterschiede in der Häufigkeit zwischen Frauen mit und ohne nachfolgender Frühgeburt fanden [44].…”
Section: Diskussionunclassified